2015
DOI: 10.1177/1087054715594456
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of ADHD Among Adolescent Students in Nigeria

Abstract: Given the burden of ADHD, efforts should be made to establish a system for the early identification and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
(90 reference statements)
3
9
1
Order By: Relevance
“…Combining these two prevalence ranges shows that ADHD of any severity, lies between 3.7 and 13.1%. These results agree with other research data (Ghossoub et al, 2017;Danielson et al, 2018;Umar et al, 2018), that prevalence of ADHD ranges between 8.8 and 12%. This appears to show that the instrument developed in this research might be a reliable tool in measuring ADHD symptoms, performing adequate screening in the school population at the Secondary Education stage.…”
Section: Discussionsupporting
confidence: 93%
“…Combining these two prevalence ranges shows that ADHD of any severity, lies between 3.7 and 13.1%. These results agree with other research data (Ghossoub et al, 2017;Danielson et al, 2018;Umar et al, 2018), that prevalence of ADHD ranges between 8.8 and 12%. This appears to show that the instrument developed in this research might be a reliable tool in measuring ADHD symptoms, performing adequate screening in the school population at the Secondary Education stage.…”
Section: Discussionsupporting
confidence: 93%
“…20,37 However, maternal use of psychoactive substance was associated with ADHD in other studies. 43 This discrepancy may be due to sociodemographic variation of the study subjects as evidenced by only 33 (8%) of the mothers of the study subject had ever used alcohol during pregnancy and no use of cigarette at all in our case.…”
Section: Discussioncontrasting
confidence: 53%
“…We found high prevalence rates of combined ADHD of 20.21%, hyperactivity-impulsivity of 9.58% and inattention of 10.83%. These rates were higher than those reported in other studies (6,13,14,16). For example, in Turkey, a study of 1508 schoolchildren aged 6-14 years showed a prevalence of 8% for combined ADHD, 20% for inattentive subtype and 14.3% for hyperactive-impulsive subtype (6).…”
Section: Discussionmentioning
confidence: 77%